156k views
4 votes
F(x) = |3x+5| + 6

g(x) =7

find (f+g) (x)

User AxelH
by
4.6k points

1 Answer

3 votes

Answer:

(f + g)(x) = |3x + 5| + 13

Explanation:

Given

f(x) = |3x + 5| + 6

g(x) = 7

Required

Find (f + g)(x)

In functions

(f + g)(x) = f(x) + g(x)

Meaning that, we simply add the given functions together

So, we have that:

(f + g)(x) = |3x + 5| + 6 + 7

(f + g)(x) = |3x + 5| + 13

Hence, (f + g)(x) when calculated equals |3x + 5| + 13

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.